2021
DOI: 10.17113/ftb.59.03.21.6846
|View full text |Cite
|
Sign up to set email alerts
|

Increased γ-Aminobutyric Acid Content of Germinated Brown Rice Produced in Membrane Reactor

Abstract: Research background. Rice germination is a natural approach to enhance the physical and functional properties of brown rice. Thus, the aim of this study was to investigate the influence of germination methods on functional properties of GBR and evaluate the process feasibility. Experimental approach. Brown rice of IPB 3S was germinated in three (3) different methods, such as (i) complete soaking without water replacement, (ii) complete soaking with water replacement every six hours, and (iii) complete soaking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…It is well known that the GABA concentration in BR significantly increases after soaking and germination. However, the GABA content in GBR varies with different types of rice and germination processes (Yao et al ., 2008; Munarko et al ., 2021; Sitanggang et al ., 2021; Munarko et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that the GABA concentration in BR significantly increases after soaking and germination. However, the GABA content in GBR varies with different types of rice and germination processes (Yao et al ., 2008; Munarko et al ., 2021; Sitanggang et al ., 2021; Munarko et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Sitanggang et al . (2021) found that germination changes the phenolic content, antioxidant capacity and γ‐oryzanol content. However, more studies on the compositional and functional changes of the bioactive components during germination are still needed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The germination of brown rice can enhance nutritional value and physiological function of brown rice (Munarko et al., 2021; Sitanggang et al., 2021). Germinated brown rice (GBR) is rich in phenolics, GABA, minerals, and other active substances which are superior to that of brown rice and white rice, and has a good effect on the prevention of diabetes, high blood fat, hypertension and other chronic diseases (Munarko et al., 2022; Li et al., 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…Germinated brown rice (GBR) has recently gained popularity in Asia. Germinated rice contains higher quantities of phytochemicals, including GABA, tocopherol, 𝛾-oryzanol, and phenolic compounds than non-germinated rice [ 10 , 11 ]. Germinated grain products have been used as new ingredients in the food industry for improving flavor, taste, mineral absorption, and nutritional value.…”
Section: Introductionmentioning
confidence: 99%